Current Drugs and Nutraceuticals for the Treatment of Patients with Dyslipidemias - Scognamiglio, Michele; Costa, Dario; Sorriento, Antonio; Napoli, Claudio (Current Pharmaceutical Design, 2019)
Coronary heart disease (CHD) remains the leading cause of disability and death in industrialized Countries. Among many conditions, which contribute to the etiology and progression of CHD, the presence of high low density lipoprotein-cholesterol (LDL-C) levels represents the major risk factor. Therefore, the reduction of LDL-C levels plays a key role in the management of patients with high or very high cardiovascular risk. Although statins represent the gold standard therapy for the reduction of cholesterol levels, these drugs do not allow to achieve target levels of LDL-C in all patients. Indeed, a significant number of patients resulted intolerants, especially when the dosage increased. The availability of new lipid-lowering drugs, such as ezetimibe and PCSK9 inhibitors, may represent an important alternative or complement to the conventional lipid-lowering therapies. However, long-term studies are still needed to define both efficacy and safety of use of these latter new drugs. Some nutraceuticals may become an adequate and effective support in the management of some patients. To date, several nutraceuticals with different mechanism of actions that provide a good tolerability are available as lipidlowering agents. In particular, the most investigated are red yeast rice, phytosterols, berberine, beta-glucans and soy. The aim of this review was to report recent data on the efficacy and safety of principle hypocholesterolemic drugs available and to evaluate the possible role of some nutraceuticals as support therapy in the management of patients with dyslipidemias.
Keywords: cardiovascular disease